Doing Business 2009 : Comparing Regulation in 181 Economies - International Finance Corporation; World Bank (Washington, DC : World Bank and Palgave Macmillon, 2012)
Doing Business 2009 is the sixth in a series of annual reports investigating the regulations that enhance business activity and those that constrain it. Doing Business presents quantitative indicators on business regulations and the protection of property rights that can be compared across 181 economies from Afghanistan to Zimbabwe and over time. Regulations affecting 10 stages of the life of a business are measured: starting a business, dealing with construction permits, employing workers, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, and closing a business. Data in Doing Business 2009 are current as of June 1, 2008. The indicators are used to analyze economic outcomes and identify what reforms have worked, where, and why. The methodology for the legal rights of lenders and borrowers, part of the getting credit indicators, changed for Doing Business 2009. The paper includes the following headings: overview, starting a business, dealing with construction permits, employing workers, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts, and closing a business.